MANAJEMEN PEMBELAJARAN PONDOK PESANTREN DALAM MEWUJUDKAN PEMAHAMAN SANTRI TERHADAP KITAB KUNING - Mubah, Hilmi Qosim (re-JIEM (Research Journal of Islamic Education Management), 2021)
This study indicates that learning is carried out with a series of activities consisting of the preparation, implementation, and closing stages. Understanding student's level consists of (1) high, (2) moderate, (3) low. Assessment criteria (a) reading according to language rules, (b) the position of a word, (c) text understanding.